2004
DOI: 10.1176/appi.ajp.161.8.1488
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Cortisol for Symptoms of Posttraumatic Stress Disorder

Abstract: The results of this pilot study indicate that low-dose cortisol treatment reduces the cardinal symptoms of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
184
3
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(206 citation statements)
references
References 8 publications
11
184
3
8
Order By: Relevance
“…Even though propranolol was found to attenuate physiological responding (heart rate and SCL) to traumatic scripts in PTSD patients (Brunet et al 2008), we did not find such effects to negative emotional scripts in healthy young men. These results also contrast the finding by Het and Wolf (2007) that cortisol can affect the emotional experience of negative events and the finding that cortisol can reduce the intensity of traumatic memories (Aerni et al 2004). However, methodological differences between these studies and our study might have caused these conflicting findings, as we will discuss below.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Even though propranolol was found to attenuate physiological responding (heart rate and SCL) to traumatic scripts in PTSD patients (Brunet et al 2008), we did not find such effects to negative emotional scripts in healthy young men. These results also contrast the finding by Het and Wolf (2007) that cortisol can affect the emotional experience of negative events and the finding that cortisol can reduce the intensity of traumatic memories (Aerni et al 2004). However, methodological differences between these studies and our study might have caused these conflicting findings, as we will discuss below.…”
Section: Discussioncontrasting
confidence: 99%
“…However, reconsolidation of emotional memories could possibly take longer than a few hours, and longer-acting doses might, therefore, be needed to affect these reconsolidation processes. Cortisol on the other hand, was given in lower doses in the clinical studies by Aerni et al (2004) and Schelling et al (2004), but the doses were given daily instead of once, leading to active cortisol during potentially multiple memory reactivations. While in the present study the dose may have been too low or shortacting to obtain reductions in physiological arousal in response to personalized scripts, in the same population as the present study, we did find long-term impairing effects of the 35-mg cortisol dose on declarative memory retrieval (Tollenaar et al 2008c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the dysfunction in these disorders is related to the inability to normally extinguish fear. Recent clinical studies showed that PTSD patients often appear to have reduced cortisol levels (Yehuda et al, 2004) and daily cortisol administration reduced symptoms of traumatic memory in PTSD patients (Aerni et al, 2004). These results suggest that brain glucocorticoid is involved in the dysregulation of fear memory extinction.…”
Section: Discussionmentioning
confidence: 90%
“…Recent clinical studies showed that PTSD patients often appear to have reduced cortisol levels (Yehuda et al, 2004). Aerni et al (2004) found that daily administration of cortisol reduced symptoms of traumatic memory in PTSD patients. Schelling et al (2004) showed that prolonged high-dose glucocorticoid treatment after trauma reduced the risk of humans developing PTSD.…”
Section: Introductionmentioning
confidence: 99%